Critical thinking and the effect in students in advanced levels of the Foreign Languages Departament - Morales Orellana, Yalin Elizabeth; Mancía Monroy, Gloria María (2024)
Why is it important for university students to study critical thinking? It is a question that can be approached from different perspectives. From a purely etymological point of view, it reveals its importance from the Greek and Latin roots of which words like "critical" and "thought” are derived. At the social level, the development of critical thinking reveals its importance for the fundamental role it plays in social processes of democratic nature in which the formation of conscious and responsible citizens is possible. From a pedagogical perspective, this issue, along with its importance, It is supported by institutions like the United Nations Educational, Scientific, and Cultural Organization (UNESCO), which formulates the guiding principles for university education, in which the development of thinking occupies a critical role. Taking the etymology of the word, “critical” comes from the Greek Kritikós, meaning "critical, well-judging (from Krino, Judging, distinguish)”. Critical is specifically defined in the dictionary of Greek roots of Castilian vocabulary as "related to crisis or to the criticism, who performs criticism" (p. 431). Such definition is a crucial link with another Greek root word “Krísis” as defined in the dictionary as "judgement, decision”. This link established from the etymology of the word reveals the relationship between crisis and critical. In a globalized world, where advances in science, changing values and the diversity of ways of understanding the world at all levels make the crisis a constant condition. The word “thinking” refers to “think from the Latin pensare; think, consider, discuss, examine something good in order to judge" (Royal Spanish Academy of Language, 1970). This definition specifies that thinking is a verb; it is related to concepts such as crisis, and critical thinking. Thinking critically has a fundamental role in a world that is hit by a crisis in all orders, social, politic, and economic that constantly demands the presence of more men and women capableof acting with responsibility in the search for solutions to all kinds of conflicts. Good criticism is not just a definition; it is a demand of what is expected from all and each who feels identified directly or indirectly with the crisis that is affecting our world. From the pedagogical aspect, Lipmann (1990) focuses on the importance of critical thinking study and its development in the formation of responsible citizens that must be reflective and not just informed, capable of responding correctly to the problematic situations; this could only be possible in a society in which education plays its role in the development of thinking and not just learning. Education, in terms of learning, treats the student like someone more passive than active, underestimating the student’s capacity to research which is the fundamental condition to the development of critical thinking. The United Nations Educational, Scientific, and Cultural Organization (UNESCO) stated at the world conference on higher education in the XXI century (UNESCO 1999) that critical thinking is one of the fundamental principles for higher education.